ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ҚЫРЫҚ ҚЫЗ» – ЖАСЛАРДЫ ЎАТАНСҮЙИЎШИЛИККЕ ТӘРБИЯЛАЎДА ТИЙКАРҒЫ ДЕРЕК - Оразымбетов, Е.К.; Сапаров, А.Т. (FAN va JAMIYAT, 2020)
The article tells about the Karakalpak people's heroic dastan "Kirik kiz (Forty girls)", which depicts the past and history of our people, about raising children, their hard work, morality, uniting forces against the enemy, the struggle for the freedom of their homeland, the patriotism of heroes, military teaching skill, law, labor, beauty, signs of humanity.